Influenza A Virus Protein NS1 Exhibits Strain-Independent Conformational Plasticity - Mitra, Sayantan (J Virol, 2019)
Influenza A virus (IAV) nonstructural protein 1 (NS1), a potent antagonist of the host immune response, is capable of interacting with RNA and a wide range of cellular proteins. NS1 consists of an RNA-binding domain (RBD) and an effector domain (ED) separated by a flexible linker region (LR). H5N1-NS1 has a characteristic 5-residue deletion in the LR, with either G (minor group) or E (major group) at the 71st position, and non-H5N1-NS1 contains E71 with an intact linker. Based on the orientation of the ED with respect to the RBD, previous crystallographic studies have shown that minor group H5N1-NS1(G71), a non-H5N1-NS1 [H6N6-NS1(E71)], and the LR deletion mutant H6N6-NS1(Δ80-84/E71) mimicking the major group H5N1-NS1 exhibit “open,” “semiopen,” and “closed” conformations, respectively, suggesting that NS1 exhibits a strain-dependent conformational preference. Here we report the first crystal structure of a naturally occurring H5N1-NS1(E71) and show that it adopts an open conformation similar to that of the minor group of H5N1-NS1 [H5N1-NS1(G71)]. We also show that H6N6-NS1(Δ80-84/E71) under a different crystallization condition and H6N6-NS1(Δ80-84/G71) also exhibit open conformations, suggesting that NS1 can adopt an open conformation irrespective of E or G at the 71st position. Our single-molecule fluorescence resonance energy transfer (FRET) analysis to investigate the conformational preference of NS1 in solution showed that all NS1 constructs predominantly exist in an open conformation. Further, our coimmunoprecipitation and binding studies showed that they all bind to cellular factors with similar affinities. Taken together, our studies suggest that NS1 exhibits strain-independent structural plasticity that allows it to interact with a wide variety of cellular ligands during viral infection. IMPORTANCE IAV is responsible for several pandemics over the last century and continues to infect millions annually. The frequent rise in drug-resistant strains necessitates exploring novel targets for developing antiviral drugs that can reduce the global burden of influenza infection. Because of its critical role in the replication and pathogenesis of IAV, nonstructural protein 1 (NS1) is a potential target for developing antivirals. Previous studies suggested that NS1 adopts strain-dependent “open,” “semiopen,” and “closed” conformations. Here we show, based on three crystal structures, that NS1 irrespective of strain differences can adopt an open conformation. We further show that NS1 from different strains primarily exists in an open conformation in solution and binds to cellular proteins with a similar affinity. Together, our findings suggest that conformational polymorphism facilitated by a flexible linker is intrinsic to NS1, and this may be the underlying factor allowing NS1 to bind several cellular factors during IAV replication.